Lejeuneaceae subfamily Ptychanthoideae (Marchantiophyta) in Thailand - Soonthree Kornochalert (2018)
Twelve genera, 37 species, and three varieties of Ptychanthoideae are known in Thailand, including four new records, Archilejeunea kiushiana (Horik.) Verd., Lopholejeunea soae R.-L. Zhu & Gradst., Schiffneriolejeunea polycarpa (Nees) Gradst., and Schiffneriolejeunea túmida var. haskarliana (Gottsche) Gradst. et Terken. Thysananthus aculeatus Herzog is excluded from Thailand. A key, brief descriptions and selected illustrations for the species of Ptychanthoideae of Thailand are provided. © 2012 Adac. Tous droits réservés.